Bayesian species delimitation in Pleophylla chafers (Coleoptera) - The importance of prior choice and morphology - Eberle, Jonas; Warnock, Rachel C. M.; Ahrens, Dirk (BMC Evolutionary Biology, 2016)
Background: Defining species units can be challenging, especially during the earliest stages of speciation, when phylogenetic inference and delimitation methods may be compromised by incomplete lineage sorting (ILS) or secondary gene flow. Integrative approaches to taxonomy, which combine molecular and morphological evidence, have the potential to be valuable in such cases. In this study we investigated the South African scarab beetle genus Pleophylla using data collected from 110 individuals of eight putative morphospecies. The dataset included four molecular markers (cox1, 16S, rrnL, ITS1) and morphometric data based on male genital morphology. We applied a suite of molecular and morphological approaches to species delimitation, and implemented a novel Bayesian approach in the software iBPP, which enables continuous morphological trait and molecular data to be combined. Results: Traditional morphology-based species assignments were supported quantitatively by morphometric analyses of the male genitalia (eigenshape analysis, CVA, LDA). While the ITS1-based delineation was also broadly congruent with the morphospecies, the cox1 data resulted in over-splitting (GMYC modelling, haplotype networks, PTP, ABGD). In the most extreme case morphospecies shared identical haplotypes, which may be attributable to ILS based on statistical tests performed using the software JML. We found the strongest support for putative morphospecies based on phylogenetic evidence using the combined approach implemented in iBPP. However, support for putative species was sensitive to the use of alternative guide trees and alternative combinations of priors on the population size (θ) and rootage (τ 0 ) parameters, especially when the analysis was based on molecular or morphological data alone. Conclusions: We demonstrate that continuous morphological trait data can be extremely valuable in assessing competing hypotheses to species delimitation. In particular, we show that the inclusion of morphological data in an integrative Bayesian framework can improve the resolution of inferred species units. However, we also demonstrate that this approach is extremely sensitive to guide tree and prior parameter choice. These parameters should be chosen with caution - if possible - based on independent empirical evidence, or careful sensitivity analyses should be performed to assess the robustness of results. Young species provide exemplars for investigating the mechanisms of speciation and for assessing the performance of tools used to delimit species on the basis of molecular and/or morphological evidence.
CRIS-Team Scopus Importer:2020-10-13
Keywords: Aedeagus; Bayesian species delimitation; Eigenshape analysis; Integrative taxonomy; Phylomorphospace; Scarabaeidae; Speciation